Operando SXRD study of the structure and growth process of Cu2S ultra-thin films - Andrea Giaccherini (Nature Portfolio, 2017)
Abstract Electrochemical Atomic Layer Deposition (E-ALD) technique has demonstrated to be a suitable process for growing compound semiconductors, by alternating the under-potential deposition (UPD) of the metallic element with the UPD of the non-metallic element. The cycle can be repeated several times to build up films with sub-micrometric thickness. We show that it is possible to grow, by E-ALD, Cu2S ultra-thin films on Ag(111) with high structural quality. They show a well ordered layered crystal structure made on alternating pseudohexagonal layers in lower coordination. As reported in literature for minerals in the Cu-S compositional field, these are based on CuS3 triangular groups, with layers occupied by highly mobile Cu ions. This structural model is closely related to the one of the low chalcocite. The domain size of such films is more than 1000 Å in lateral size and extends with a high crystallinity in the vertical growth direction up to more than 10 nm. E-ALD process results in the growth of highly ordered and almost unstrained ultra-thin films. This growth can lead to the design of semiconductors with optimal transport proprieties by an appropriate doping of the intra metallic layer. The present study enables E-ALD as an efficient synthetic route for the growth of semiconducting heterostructures with tailored properties.